Religious Coping and Gratitude in Emerging Adulthood - Brelsford, Gina M. (Research in the social scientific study of religion, 2014)
This study focused on understanding how emerging adults’ use of religious coping strategies related to a grateful disposition. A sample of 319 college students provided responses related to their use of coping strategies, including religious and secular coping coupled with measures of personality, satisfaction with life, affect, and gratitude. Results indicated emerging adults who reported higher levels of positive religious coping strategies also indicated higher levels of gratitude. Conversely, respondents reported an inverse correlation between negative religious and self-directed religious coping and gratitude. Using hierarchical regression analyses, we found that religious coping, specifically negative religious coping, predicted participants’ gratitude even after accounting for subjective well-being, secular coping, and personality factors. Implications for these findings are discussed in light of challenges faced by emerging adults today.